Israel : Financial System Stability Assessment, including Reports on the Observance of Standards and Codes on the following topics; Monetary and Financial Policy Transparency; Banking Supervision; Securities Supervision; and Payments Systems. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2001)
The recent government administrations and the Bank of Israel (BOI) are determined to obtain and preserve a stable currency and macroeconomic environment, in addition to deepening the financial sector. The BOI plays a key role in liquidity management and absorbing liquidity shocks owing to the uneven development of financial markets. The paper summarizes assessment of Israel's observance of financial sector supervision standards and codes. Israel has relatively well-developed, capable, and transparent financial sector supervision and monetary policy formulation. Insurance and pension reform should be completed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet